2018
DOI: 10.1002/jsfa.9270
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and phenolic composition in pomegranate (Punica granatum L.) genotypes from south Italy by UHPLC–Orbitrap‐MS approach

Abstract: The UHPLC-Orbitrap-MS approach was employed for the first time to identify the phenolic compound profiling in five pomegranate genotypes. TAA was analysed using an ABTS assay, and the results showed a significant variability in nutraceutical potential of the pomegranate genotypes studied. The inclusion of phenolic information in the linear discriminant analysis allowed very good discriminations among genotypes to be obtained. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
5
52
0
Order By: Relevance
“…Non‐flavonoid compounds are mainly phenolic acids, including hydroxycinnamic acid and hydroxybenzoic acid. The amounts of phenolic compounds can be affected by cultivar, geographical region, ripening stages and extraction process …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Non‐flavonoid compounds are mainly phenolic acids, including hydroxycinnamic acid and hydroxybenzoic acid. The amounts of phenolic compounds can be affected by cultivar, geographical region, ripening stages and extraction process …”
Section: Introductionmentioning
confidence: 99%
“…In the study reported here, five sweet cherry cultivars, Caihong, Sunburst, Summit, 23–51 and Valeri, taking into account their peel and flesh, were tested for phenolic characteristics. Phenolic compounds, including free, soluble conjugated and insoluble bound fractions, were qualitatively and quantitatively examined using ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) . As far as we know, this is the first study focusing on the determination of phenolics using UPLC‐MS/MS in peel and flesh of sweet cherries separately.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such compounds have antioxidant (Banihani, Shuaibu, Al-Husein, & Makahleh, 2019;Di Stefano et al, 2018), anti-carcinogenic (Sharma et al, 2017), anti-atherogenic (Rosenblat, Volkova, Borochov-Neori, Judeinstein, & Aviram, 2015), anti-inflammatory (Cho & Song, 2018), antihypertensive (Stowe, 2011), and antihyperglycemic effects (Banihani et al, 2014). Such compounds have antioxidant (Banihani, Shuaibu, Al-Husein, & Makahleh, 2019;Di Stefano et al, 2018), anti-carcinogenic (Sharma et al, 2017), anti-atherogenic (Rosenblat, Volkova, Borochov-Neori, Judeinstein, & Aviram, 2015), anti-inflammatory (Cho & Song, 2018), antihypertensive (Stowe, 2011), and antihyperglycemic effects (Banihani et al, 2014).…”
mentioning
confidence: 99%